Semantic interoperability based on Dublin Core hierarchical one-to-one mappings. (7th February 2007) - Tolosana-Calasanz, R.; Nogueras-Iso, J.; Bejar, R.; Muro-Medrano, P.R.; , F.J. Zarazaga-Soria
The tendency of current cataloguing systems is to interchange metadata in XML according to the specific standard required by each user on demand. Furthermore, metadata schemas from different domains are not usually semantically distinct but overlap and relate to each other in complex ways. As a consequence, the semantic interoperability has to deal with the equivalences between those descriptions. There exist two main approaches in order to tackle this problem: solutions based on the use of ontologies and solutions based on the creation of specific crosswalks for one-to-one mapping. This paper proposes a hierarchical one-to-one mapping solution for improving semantic interoperability.